PELATIHAN PENGELOLAAN SAMPAH SEBAGAI WUJUD PENGEMBANGAN EKOWISATA BERBASIS MANGROVE DI PANTAI GLAGAH WANGI KABUPATEN DEMAK - Listyorini, Sari; Prabawani, Bulan; Wijayanto, Andi; Pinem, Robetmi Jumpakita (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Nature tourism requires precision in managing it into a decent destination and has a high attractiveness. The previously owned potential becomes the impetus for better management. Glagah Wangi Beach is a type of marine tourism located in Demak. The attractions are in the form of a beach area, mangroves, and several beach rides. With the development of beaches with many tourist visits, new problems will arise, namely garbage that pollutes the beach area and has not been managed properly by tourism managers. Improvements are made around waste management for the realization of this destination as ecotourism tourism. Community-based management which is the focus of this activity aims to build the capacity of the local village community to continue to exist in the management of the ecotourism tourism industry. This community service is carried out in multi-years for 3 years with the first year's activities being to develop ecotourism potential through tourism waste management awareness through training in the manufacture of liquid fertilizer and composting. The goal is that people are aware of cleanliness and are able to utilize waste and beach waste into useful products. The result of this community service is an increase in knowledge, community insight in waste management, especially the manufacture of liquid fertilizer and composting. Keywords: waste management training; liquid fertilizer; composting; ecotourism